Meaning (De)Construction Through the (Re)Presentation of an Actor and Character in Gintaras Varnasʼ Staging - Meilutytė, Monika (Jaunųjų mokslininkų darbai, 2015)
The aim of the paper is to analyze and evaluate how meaning is being constructed or deconstructed through the (re) presentation of an actor and the character he plays in the performances staged by Gintaras Varnas. Research methods: narratological analysis, comparative analysis. Aso the theories and concepts of structuralists and post structuralists were used while forming the theoretical tools for this research.The research showed that in the works of Gintaras Varnas an actor has to fulfil a traditional function – to create a fictional character who is part of the semantic layer of the performance revealing a nonhomogeneous personality. Other means that help an actor reveal heterogeneity of the character he is playing are also used, for instance, the intense relationship between an actor’s playing and video projections.It was also noticed that an actor usually has to manipulate different layers of a narrative and create a „play within a play“. In this way an actor constructs a narrative using not only diegetic mimesis but also its shifts. Moreover, an actor and the character he is playing merge truthfulness and dreaminess which are especially important in the works of this stage director.Thus the elements both sustaining the concord of the whole performance and disassembling it are being created through the (re)presentation of an actor and character in Gintaras Varnasʼ performances.
Keywords: theatre; (de)construction; meaning; actor; (re)presentation; Gintaras Varnas